Measuring Inequity Aversion in a Heterogeneous Population Using Experimental Decisions and Subjective Probabilities - Bellemare, Charles; Kröger, Sabine; van Soest, Arthur (Econometrica, 2008)
We combine choice data in the ultimatum game with the expectations of proposers elicited by subjective probability questions to estimate a structural model of decision making under uncertainty. The model, estimated using a large representative sample of subjects from the Dutch population, allows both nonlinear preferences for equity and expectations to vary across socioeconomic groups. Our results indicate that inequity aversion to one's own disadvantage is an increasing and concave function of the payoff difference. We also find considerable heterogeneity in the population. Young and highly educated subjects have lower aversion for inequity than other groups. Moreover, the model that uses subjective data on expectations generates much better in- and out-of- sample predictions than a model which assumes that players have rational expectations.